Efecto del COVID-19 en el sistema de intermediación financiera: El caso boliviano - Osvaldo Nina Baltazar (Institute for Advanced Development Studies (INESAD), 2021)
– The coronavirus pandemic has generated a long-term recession, the impact of which no country has been able to avoid, regardless of the containment strategy implemented. The financial intermediation system has been among the hardest hit because the economic consequences materialized in just two weeks after the declaration of national health emergency and quarantine. Therefore, the objective of the study is to estimate the effect of COVID-19 on the performance of financial intermediation entities by analyzing financial statements and estimating residual regression models with monthly data for a group of 56 institutions. The findings show that containment measures have had negative effects on financial indicators, especially profitability.
Keywords: C33; G21; G28; 330; Bolivia; coronavirus; crisis; financial intermedia